HERITAGE EDUCATION: NEED OF THE HOUR - OJHA, SEEMA (THE PRIMARY TEACHER, 2012)
The general notion of the term ‘heritage’ is associated with monuments and relics with historical value and is often limited to (passive) visits to monuments or museums. Since the 1970s care for heritage has played an increasingly important role in some societies and the phenomenon of heritage has extended by including non-material heritage such as folk tales or traditions, and landscapes. Through new pedagogical approaches, such as cross-curricular collaboration and project work, several western countries have been successful in implementing heritage education in their schools but inspite of its mention in all Indian curriculum frameworks for schools until recently a general introduction to heritage education in an Indian context was missing. CBSE recently launched several programmes to promote heritage education in schools but still there is a long way to go. This article talks about what heritage is, its place in the school curriculum, meaning and importance of heritage education in our schools and some exemplary activities to promote heritage education in schools, etc.